Spatial Pattern of Functional Urban Land Conversion and Expansion under Rapid Urbanization: A Case Study of Changchun, China - Guolei Zhou; Jing Zhang; Chenggu Li; Yanjun Liu (Land, 2022)
As populations continue to be concentrated in cities, the world will become entirely urbanized, and urban space is undergoing a drastic evolution. Understanding the spatial pattern of conversion and expansion of functional urban land, in the context of rapid urbanization, helps us to grasp the trajectories of urban spatial evolution in greater depth from a theoretical and practical level. Using the ESRI ArcGIS 9.3 software platform, methods, such as overlay analysis, transition matrix, and kernel density estimation, were used in order to analyze the spatiotemporal characteristics of different types of functional urban land conversion and expansion in the central city of Changchun. The results show that different types of functional urban land were often expanded and replaced, and the urban spatial structure was constantly evolving. The conversion and expansion of functional urban land show similar characteristics to concentric zone and sector modes and show dynamic changes in different concentric circles and directions at different periods. Our method can accurately identify the different types of functional urban land, and also explore the evolutionary trajectory of urban spatial structure. This study will help to coordinate the development of different functional urban spaces and to optimize the urban spatial structure in the future.